The Relationship Between Emotional Intelligence and Internet Addiction Among Youth and Adults. Issue 1 (January 2018) - Saraiva, Jorge; Esgalhado, Graça; Pereira, Henrique; Monteiro, Samuel; Afonso, Rosa Marina; Loureiro, Manuel
Abstract : Abstract: This study aimed to compare emotional intelligence (EI) levels and Internet addiction (IA) by gender and age groups and to assess the predictive relationship between EI and IA. One thousand four hundred thirteen young people and adults participated in the study. Participants were between 17 and 81 years old ( M = 38.70 years old, SD = 13.72 years old); 42.2% were male, whereas 57.5% were female. We used a sociodemographic questionnaire, the Schutte Emotional Intelligence Scale (Schutte, Malouff, & Bhullar, 2009), and the Internet Addiction Test (Young, 1998) as data collection instruments. Results showed that there is a weak, but statistically significant, negative relationship between EI and IA. We found higher levels of EI in older people and in women than in the youngest participants and in men. No relevant prevalence of IA was found in the participants of this study.